Catalan Identity and Paradiplomacy Strategy in Catalonia’s Independence Movement - Dermawan, Windy; Akim, Akim (Global: Jurnal Politik Internasional, 2020)
This article seeks to analyse how Catalan identity, within the context of its conflict with the Spanish government, contributes to its foreign relations with the global public through paradiplomacy. This article uses qualitative research method with literature study. It finds that Catalonia, as one of Spain’s autonomous regions, have a distinct history, language, and culture from other Spanish regions. To protect their identity, there have been an emergence of movement for greater Catalan autonomy, even independence. This conflict reached climax on 1 October 2017 when the Catalan government initiated an independence referendum amongst Catalan people, with the majority voted for independence from Spain. Since then, the Catalan independence movement has faced many changes until now, with one of the moves done by Catalonia to seek support from global public through their paradiplomacy. As such, it is worth noting how paradiplomacy done by the Catalan government was an effort to protect the existence of their identity, which increases the complication and dynamics of Catalan and Spanish governments’ internal conflict. Findings from this study may show important implications for the resolution of similar internal conflicts, especially those involving identity and paradiplomacy.